Respuesta :
Answer:
The new frequency = [tex]\frac{f_0}{3}[/tex].
Step-by-step explanation:
Consider the provided information.
The formula for the frequency is:
[tex]f=\frac{1}{2\pi}\sqrt{\frac{k}{m}}[/tex]
Where k is the spring constant.
The mass oscillates with a frequency [tex]f_0[/tex].
[tex]f_0=\frac{1}{2\pi}\sqrt{\frac{k}{m_0}}[/tex]
It is given that the mass is replaced with a mass nine times as large.
So replace [tex]m_0 = 9m_0[/tex] as shown.
[tex]f_N=\frac{1}{2\pi}\sqrt{\frac{k}{9m_0}}[/tex]
[tex]f_N=\frac{1}{2\pi}\times\frac{1}{3}\sqrt{\frac{k}{m_0}}\\f_N=\frac{1}{3}\times\frac{1}{2\pi}\sqrt{\frac{k}{m_0}}\\f_N=\frac{1}{3}\times f_0}}[/tex]
Here, [tex]f_N[/tex] represents the new frequency.
Hence, the new frequency = [tex]\frac{f_0}{3}[/tex].
The mass is replaced with a mass nine times as large. Then the new frequency is [tex]\dfrac{f_o}{3}[/tex].
What is the frequency?
The rate at which something occurs in a particular time period.
The formula for the frequency is given as
[tex]f = \rm \dfrac{1}{2\pi} \sqrt{\dfrac{k}{m}}[/tex]
Where k is the spring constant.
The mass oscillates with a frequency [tex]f_o[/tex] that will be
[tex]f_o = \rm \dfrac{1}{2\pi} \sqrt{\dfrac{k}{m_o}}[/tex]
It is given that the mass is replaced with a mass nine times as large. Then
[tex]f_N = \dfrac{1}{2\pi} \sqrt{\dfrac{k}{9m_o}}\\\\\\f_N = \dfrac{1}{2\pi} * \dfrac{1}{3} \sqrt{\dfrac{k}{m_o}}\\\\\\f_N = \dfrac{1}{3} f_o[/tex]
Here, [tex]f_N[/tex] represents the new frequency.
Thus, the new frequency is [tex]\dfrac{f_o}{3}[/tex].
More about the frequency link is given below.
https://brainly.com/question/14926605